Test-retest variability of visual acuity in a busy eye clinic - Khantsi, B (My University, 2016)
OBJECTIVES The main objective is to demonstrate and to quantify any variability between nurse measured and doctor measured visual acuity (VA) performed on the same patient under the same testing conditions in the out patients clinic at the St John Eye Hospital. DESIGN A prospective, cross-sectional study using adult patients presenting with visual acuity of at least 6/60 in one eye as measured on an illuminated Snellen chart. The study was performed on patients aged 18 years and older. STUDY METHOD Patients who have had VA testing by the nurses but have not consulted with the doctors were randomly selected to have their VA re-tested by a doctor under the same testing conditions as the initial testing by the nurses. Both tests were performed using an illuminated Snellen chart. STATISTICAL METHODS Using a Bland-Altman analysis, a measurement error between the two observers was determined. The difference in measurements between observers for each patient was determined and each value was plotted on the y-axis. The mean difference in observations was in-turn calculated and plotted on the x-axis. The degree of disagreement with its 95% confidence interval (CI) was plotted on the graph. VI RESULTS The calculated difference in Early Treatment of Diabetic Retinopathy Study (ETDRS) letters between the observers ranged between 0 and 55 letters, which equates to 11 Snellen lines. When the differences are averaged out, the mean difference was only 0.045 letters with a standard deviation of 9.62 letters and the 95% confidence interval (CI) of -55 to 70. On performing the Bland-Altman analysis, the limits of agreement between the observers at the 95% CI were -18.79 letters (at lower end) and 19.70 letters (at the upper end), a total of 38.49 ETDRS letters. CONCLUSIONS The VAs measured at the St John Eye Hospital out patients department are not reproducible. Variability in measurement as found in the study was 38,49 ETDRS letters, an equivalent of 7,69 Snellen lines. This is not within the accepted limit of 2 Snellen lines or 10 ETDRS letters.
Registered for: MMed Ophthalmology Division of Ophthalmology Department of Neurosciences University of the Witwatersrand